Decreased Phase–Amplitude Coupling Between the mPFC and BLA During Exploratory Behaviour in Chronic Unpredictable Mild Stress-Induced Depression Model of Rats - Wang, Zihe; Cao, Qingying; Bai, Wenwen; Zheng, Xuyuan; Liu, Tiaotiao (Frontiers in Behavioral Neuroscience, 2021)
Depression is a common neuropsychiatric illness observed worldwide, and reduced interest in exploration is one of its symptoms. Dysregulated medial prefrontal cortex (mPFC) control over the basolateral amygdala (BLA) is related to depression. However, the oscillation interaction in the mPFC-BLA circuit has remained elusive. Therefore, this study used phase-amplitude coupling (PAC), which provides complicated forms of information transmission by phase of low frequency rhythm modulating the amplitude of high frequency rhythm and has potential application for the treatment of neurological disease. The chronic unpredictable mild stress (CUMS) was used to prepare the rat models of depression. Moreover, multichannel in vivo recording was applied to obtain the local field potentials (LFPs) of the mPFC and BLA in rats in control and CUMS groups while they explored the open field. The results showed prominent coupling between the phase of theta oscillation (4-12 Hz) in the mPFC and the amplitude of high gamma oscillation (70-120 Hz) in the BLA. Compared to the control group, this theta-gamma PAC was significantly decreased in the CUMS group, which was accompanied by the diminished exploratory behaviour. The results indicate that the coupling between the phase of theta in the mPFC and the amplitude of gamma in the BLA is involved in exploratory behaviour, and this decreased coupling may inhibit exploratory behaviour of rats exposed to CUMS.